3D graphene-based gel photocatalysts for environmental pollutants degradation. (October 2019) - Zhang, Fan; Li, Yue-Hua; Li, Jing-Yu; Tang, Zi-Rong; Xu, Yi-Jun
Abstract: Enormous research interest is devoted to fabricating three-dimensional graphene-based gels (3D GBGs) toward improved conversion of solar energy by virtue of the intrinsic properties of single graphene and 3D porous structure characteristics. Here, this concise minireview is primarily focused on the recent progress on applications of 3D GBGs, including aerogels and hydrogels, in photocatalytic degradation of pollutants from water and air, such as organic pollutants, heavy metal ions, bacteria and gaseous pollutants. In particular, the preponderances of 3D GBG photocatalysts for environmental pollutants degradation have been elaborated. Furthermore, in addition to discussing opportunities offered by 3D GBG composite photocatalysts, we also describe the existing problems and the future direction of 3D GBG materials in this burgeoning research area. It is hoped that this review could spur multidisciplinary research interest for advancing the rational utilization of 3D GBGs for practical applications in environmental remediation. Graphical abstract: Image 101229 Highlights: 3D graphene-based gels (3D GBGs) possess more active sites. Porous structure of 3D GBGs promotes the photogenerated electrons transfer. 3D framework provides an ideal support for the active components. Applications of 3D GBGs in photocatalytic environmental remediation are overviewed.